Anti-inflammatory properties of commonly used psychiatric drugs - Patel, Shrujna; Keating, Brooke A.; Dale, Russell C. (Frontiers in Neuroscience, 2023)
Mental health and neurodevelopmental disorders are extremely common across the lifespan and are characterized by a complicated range of symptoms that affect wellbeing. There are relatively few drugs available that target disease mechanisms for any of these disorders. Instead, therapeutics are focused on symptoms and syndromes, largely driven by neurotransmitter hypotheses, such as serotonin or dopamine hypotheses of depression. Emerging evidence suggests that maternal inflammation during pregnancy plays a key role in neurodevelopmental disorders, and inflammation can influence mental health expression across the lifespan. It is now recognized that commonly used psychiatric drugs (anti-depressants, anti-psychotics, and mood stabilizers) have anti-inflammatory properties. In this review, we bring together the human evidence regarding the anti-inflammatory mechanisms for these main classes of psychiatric drugs across a broad range of mental health disorders. All three classes of drugs showed evidence of decreasing levels of pro-inflammatory cytokines, particularly IL-6 and TNF-α, while increasing the levels of the anti-inflammatory cytokine, IL-10. Some studies also showed evidence of reduced inflammatory signaling via nuclear factor- (NF-)κB and signal transducer and activator of transcription (STAT) pathways. As researchers, clinicians, and patients become increasingly aware of the role of inflammation in brain health, it is reassuring that these psychiatric drugs may also abrogate this inflammation, in addition to their effects on neurotransmission. Further studies are required to determine whether inflammation is a driver of disease pathogenesis, and therefore should be a therapeutic target in future clinical trials.